2022
DOI: 10.3389/fendo.2022.937099
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones act as modulators of inflammation through their nuclear receptors

Abstract: Reciprocal crosstalk between endocrine and immune systems has been well-documented both in physiological and pathological conditions, although the connection between the immune system and thyroid hormones (THs) remains largely unclear. Inflammation and infection are two important processes modulated by the immune system, which have profound effects on both central and peripheral THs metabolism. Conversely, optimal levels of THs are necessary for the maintenance of immune function and response. Although some ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 121 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it reduces T3 availability due to the influence of cytokines on deiodinases’ activity [4]. On the other hand, THs modulate several immune responses and are thought to promote anti-inflammatory responses at physiological levels [14]. In our study, we found that lower levels of FT3/FT4 ratio and FT3 were associated with higher ESR levels, suggesting a stronger inflammatory response with lower levels of FT3.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, it reduces T3 availability due to the influence of cytokines on deiodinases’ activity [4]. On the other hand, THs modulate several immune responses and are thought to promote anti-inflammatory responses at physiological levels [14]. In our study, we found that lower levels of FT3/FT4 ratio and FT3 were associated with higher ESR levels, suggesting a stronger inflammatory response with lower levels of FT3.…”
Section: Discussionmentioning
confidence: 51%
“…Prolactin strongly elicits innate and adaptive immune responses, by promoting the maturation of Clusters of Differentiation 4 (CD4), and CD8 on surfaces of immune cells including monocytes, T helper cells, macrophages and dendritic cells, into CD4+ and CD8+ cells. Furthermore, serum prolactin levels (PRL) can alter Th1 and Th2 type cytokine production to favor interleukin (IL)-6 and interferongamma (INF-γ) secretion and also enhance immunoglobulin (Ig) production [25][26] . This could explain why pregnant women generally have weaker immunity compared to their non-pregnant counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al reported in their study, which included more than 3100 patients comprising more than 7700 patient-years, an increased risk for carotid atherosclerosis related to low-grade systemic inflammation [ 36 ]. Lasa and Contreras-Jurado argued in their review, that one explanation for this association could be the modulating function of thyroid hormones on inflammatory pathways, through their binding to specific nuclear thyroid receptors, all pointing to the close association between the thyroid hormones and inflammation [ 37 ]. This concurs with our finding of higher CRP concentration in the group with the lowest fT3 levels.…”
Section: Discussionmentioning
confidence: 99%